أساليب التدريب في اكتساب بعض المهارات الأساسية عند الناشئين - عون أحمد, د/ عدنان مقبل; سليم, د/ بزيو; عادل, أ/ بزيو (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
Sport training process  is  based on the correct scientific planning, it aims to allow to athlete.  In reaching higher Performance in different sport activities. Creativity and progress in sport training methods and tools will be accomplished by using its principles and basis, basing on scientific planning in order to dispose a global training approaches. Implementation of this approaches is accompanied byphysical, psychological an functional changes, due to the link between functional improvement of vital body sport organs and sport.. أن عملية التدريب الرياضي تعتمد على التخطيط العلمي السليم وذلك بهدف محاولة الوصول بالفرد الرياضي إلى تحقيق أعلى مستوى في نوع النشاط الرياضي الممارس. كما أن حالة الإبداع والابتكار والتطور في أساليب ووسائل التدريب الرياضي يتم من خلال استخدام أسس ومبادئ التدريب الرياضي وما تتطلبه من التخطيط العلمي لأعداد مناهج تدريبية شاملة، وأن تنفيذ هذه المناهج يصاحبه تغيرات بدنية ومهارية ونفسية ووظيفية، لأن هناك ارتباطاً مباشراً بين التحسن الوظيفي لأجهزة الجسم الحيوية والإنجاز الرياضي.